2011
DOI: 10.1053/j.gastro.2010.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Signaling and Bacterial Infection Recruit Tumor-Promoting Macrophages to Mouse Gastric Tumors

Abstract: Conflict of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 32 publications
8
95
0
Order By: Relevance
“…We recently showed that inflammatory responses and macrophage infiltration were suppressed in K19-C2mE mouse gastritis and Gan mouse tumors when mice were maintained under germfree conditions (Figure 5d and Oshima et al, 2011). Notably, miR-7 expression levels were increased significantly in germfree K19-C2mE and Gan mice compared with the levels of mice maintained in a specific pathogen free (SPF) facility (Figure 5e).…”
Section: Downregulation Of Mir-7 In the Stomach By Inflammatory Respomentioning
confidence: 91%
See 3 more Smart Citations
“…We recently showed that inflammatory responses and macrophage infiltration were suppressed in K19-C2mE mouse gastritis and Gan mouse tumors when mice were maintained under germfree conditions (Figure 5d and Oshima et al, 2011). Notably, miR-7 expression levels were increased significantly in germfree K19-C2mE and Gan mice compared with the levels of mice maintained in a specific pathogen free (SPF) facility (Figure 5e).…”
Section: Downregulation Of Mir-7 In the Stomach By Inflammatory Respomentioning
confidence: 91%
“…Moreover, the genomic region including miR-7-1 was not deleted in human gastric cancer cells (Supplementary Figure 3b), suggesting that miR-7 downregulation in gastric cancer is not caused by genomic deletion. We next examined whether activated macrophages have a role in the downregulation of miR-7, because the major source of proinflammatory cytokines in gastric tumors are macrophages (Oshima et al, 2004(Oshima et al, , 2011. To monitor miR-7 activity, reporter vector-transfected cells were used.…”
Section: Repression Of Mir-7 In Gastric Cancer Cells By Macrophage-dementioning
confidence: 99%
See 2 more Smart Citations
“…In the gastric tumors of Gan mice, macrophages infiltrate into the tumor stroma, and they are activated to express proinflammatory cytokines, chemokines, growth factors and proteases (Oshima et al 2011a). We found that the expression of EGFR ligands, including amphiregulin and epiregulin, and ADAM family proteases, is upregulated in Gan mouse tumors by an inflammation-dependent mechanism (Oshima et al 2011b).…”
Section: Tnf-α Signaling In Gan Mouse Gastric Tumorigenesismentioning
confidence: 81%